Analisis Pragmatik terhadap Dialog Tokoh dalam Cerpen Warisan untuk Doni Karya Putu Ayub - Poppy Aulia Sutarli; Gusti Yarmi; Saifur Rohman (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2026)
This study aims to analyze the pragmatic aspects found in the short story Warisan untuk Doni by Putu Ayub through the examination of locutionary, illocutionary, and perlocutionary speech acts. As a literary work, a short story functions not only as a medium of entertainment but also as a means of conveying values and life lessons to readers. Therefore, a pragmatic approach is employed to reveal the meanings, intentions, and effects of utterances expressed by the characters in the story. This research uses a qualitative descriptive method. The data source is the short story Warisan untuk Doni, which is included in the short story collection Aku, Dia, Mereka by Putu Ayub. Data were collected through reading and note-taking techniques and analyzed by identifying and classifying utterances based on the categories of locutionary, illocutionary, and perlocutionary speech acts. The findings indicate that the short story contains various forms of speech acts that function to convey information, intentions, expectations, advice, and influence the actions and responses of other characters. Locutionary acts are reflected in utterances that provide direct information, illocutionary acts appear in utterances containing specific intentions such as advising and directing, while perlocutionary acts are evident in utterances that produce effects or behavioral changes in interlocutors. The study concludes that pragmatic elements play a significant role in constructing the storyline and conveying moral values related to responsibility, hard work, and wisdom in managing life.